Urban land use fragmentation and human wellbeing - Christine Bertram; Jan Goebel; Christian Krekel; Katrin Rehdanz (Kiel Institute for the World Economy (IfW), 2020)
We study how urban land use fragmentation affects the subjective wellbeing of city residents. Therefore, we calculate fragmentation metrics based on the European Urban Atlas for 15,000 households in the German Socio-Economic Panel. Using random and fixed effects specifications, we find that fragmentation has little impact on wellbeing when aggregating over all land use types. Looking at particular land use types, however, we find that wellbeing is positively affected by lower average degrees of soil sealing, larger shares of vegetation, and a more heterogeneous configuration of medium and low density urban fabric, especially in areas with above average population density.
Keywords: C23; Q51; Q57; R20; 330; Urban Land Use; Urban Land Use Fragmentation; Subjective Wellbeing; Life Satisfaction; Spatial Analysis; SOEP; GIS